Designing the Blockchain-Integrated Collaborative E-Payment Framework - Naharudin Saadan; Khairil Faizal Khairi; Azuan Ahmad; Agoos Munalis Tahir (Universiti Sains Islam Malaysia, 2026)
Indexed by MyCite